Climate-Smart Villages: the future of farming - Ghosh, Padmaparna (2018)
This photo series and article on National Geographic Magazine highlights the principles of climate-smart agriculture through the Climate-Smart Village approach in South Asia, as also West and East Africa, South East Asia and Latin America.